Combined Laser Photocoagulation and anti-VEGF Injection Treatment in Radiation Retinopathy - Hurtikova, K.; Gerding, H. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background Radiation retinopathy can lead to a considerable reduction in visual acuity. We report 2 cases of radiation retinopathy in which a therapy with combined intravitreal anti-VEGF injection and laser photocoagulation (LPC) was used. Patient History Two 55-year-old women were referred to our clinic with radiation retinopathy, in the first case unilaterally after radiation due to endocrine orbitopathy (P1), in the second case in both eyes after palliative cerebral radiation for metastatic breast cancer (P2). Both cases were treated with combined intravitreal anti-VEGF injection and focal LPC. Therapy After the initiation therapy macular edema decreased considerably. One year after the beginning of therapy visual acuity increased in the first case from 0,05 to 0,16 p, in the second case from 0,5/0,4 to 0,6/0,5. Despite the positive response there is still continuing need for therapy in all three eyes. Conclusions Combined anti-VEGF injection and LT can reduce macular edema due to radiation retinopathy. The follow-up observation shows the necessity of long-term care.
Keywords: radiation retinopathy; anti-VEGF; laser photocoagulation